Direct photon production at low transverse momentum in proton-proton collisions at √s =2.76 and 8 TeV - Acharya, S.; Torales-Acosta, F.T.; Adamovã, D.; Adolfsson, J.; Aggarwal, M.M.; Aglieri Rinella, G.A.; Agnello, M.; Agrawal, N.; Ahammed, Z.; Ahn, S.U.; Aiola, S.; Akindinov, A.; et al. (American Physical Society, 2019)
Measurements of inclusive and direct photon production at midrapidity in pp collisions at √s = 2.76 and 8 TeV are presented by the ALICE experiment at the LHC. The results are reported in transverse momentum ranges of 0.4 < Pᴛ < 10 GeV/c and 0.3 < Pᴛ < 16 GeV/c, respectively. Photons are detected with the electromagnetic calorimeter (EMCal) and via reconstruction of e⁺e⁻ pairs from conversions in the ALICE detector material using the central tracking system. For the final measurement of the inclusive photon spectra the results are combined in the overlapping Pᴛ interval of both methods. Direct photon spectra, or their upper limits at 90% C.L. are extracted using the direct photon excess ratio Ry , which quantifies the ratio of inclusive photons over decay photons generated with a decay-photon simulation. An additional hybrid method, combining photons reconstructed from conversions with those identified in the EMCal, is used for the combination of the direct photon excess ratio Ry , as well as the extraction of direct photon spectra or their upper limits. While no significant signal of direct photons is seen over the full Pᴛ range, Ry for Pᴛ > 7 GeV/c is at least one above unity and consistent with expectations from next-to-leading order pQCD calculations.
Keywords: Physics; Photon; Spectral line; Nuclear physics; Proton; Momentum (technical analysis); Large Hadron Collider; Rapidity; Production (economics); Particle physics; Optics; Quantum mechanics; https://purl.org/pe-repo/ocde/ford#1.03.03